Study Ethnobotany Andong Plants of the Genus Cordyline in the Dayaknese of Meratus Lok Lahung Village, Loksado, South Borneo - Gunawan, Gunawan (Proceeding International Conference on Global Resource Conservation, 2013)
This research aims to inform about use plants of th egenus cordyline in the Dayaknese of Meratus, Lok Lahung village, South Borneo and documented the local cultural in the use of genus Cordyline plant. The method used is purposive sampling with a sampling intensity of 10% +3. The data was collected by surveys and interviews with semi-structural techniques. The results of this study showing plants of the genus Cordyline is a Lok Lahung village, Loksado South Borneo is red andong (Cordyline fruticosa L.) and green andong (Cordyline terminalis P.). In the Lok Lahung village have major role in their lives that is widely used in religious, rituals and beliefs, medicine.. Andong red plant parts most widely used are the leaves and stems. Leaves and stems are widely used in traditional ceremonies and rituals.Keywords: benefits of andong, ethnoanthropology, The Dayaknese of Meratus